Evaluation of Dietary Rice Bran Crude Lecithin as Substitute of Maize Grain in the Ration of Crossbred Calves - Tewari, Dharmesh (Indian Journal of Animal Nutrition, 2021)
The aim of the present experiment was to assess the potential of rice bran crude lecithin (RBCL) as an alternative energy source in the diet of growing cattle. Two experiment was conducted: in the first experiment total gas and methane production along with digestibility of dry and organic matter was measured in vitro; in the second experiment two different experimental levels of RBCL was tested on eighteen crossbred calves. Six substrate comprising of either 0 (T1), 4 (T2), 8 (T3), 12 (T4), 16 (5) or 20 (T6) % RBCL, replacing equal amount of maize grain of control were tested. Response criteria during in vitro evaluation was gas and methane production, and digestibility of dry matter and organic matter. During the second experiment, eighteen crossbred calves were randomly distributed into three groups of six each in an experiment based on completely randomized design. Calves of control group (GI) were fed a standard dietary concentrate and wheat straw to meet their nutrient requirements (ICAR, 2013). However, 8 and 12% of maize of the concentrate mixture of control group was replaced with RBCL in groups GII and GIII, respectively. The net gas production and methane production (ml/200mg), in vitro true dry matter and organic matter digestibility (%) decreased (P<0.001), while, efficiency of microbial biomass production (%) increased (P<0.001) with the increased level of RBCL. During in vivo study digestible dry matter and organic matter intake (g/kgW0.75) was significantly (P<0.05) lower in GIII as compared to GI. The intake of total digestible nutrients and digestible crude protein was comparable (P>0.05) among the groups. Although body weight gain apparently seemed to decrease with increased levels of RBCL values were comparable among the groups. Clinical chemistry profile was comparable among the groups. It was concluded that RCBL can replace up to 12% of maize grain of the concentrate mixture without any adverse impact on plane of nutrition, clinical chemistry and performance of crossbred calves.